PENDEKATAN DESIGN THINKING PROCESS DALAM PENERAPAN 5S DAN WISE UNTUK PERBAIKAN AREA KERJA - Cornelius Rakai Ahimsa Atmajaya; Yosef Daryanto (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2022)
The operations of a printing company were disrupted due to many wastes that caused delays in sending customer orders. Hence, improvement programs are designed based on the design thinking process. During the empathize phase, information from several customers, employees, and the owner are gathered focused on the difficulties they experienced and their needs as well as expectations. Further interviews and detailed observations were conducted to define the problem and set the goal. It is proceeded with the generation of several solution ideas that end with the selection of a suitable solution and method. The chosen alternative solution is improvement in the work area that based on the literature review can be realized through the implementation of 5S (seiri, seiton, seiso, seiketsu, and shitsuke) and Work Improvement in Small Enterprise (WISE) programs. Then, several data collection, analysis, and design processes were carried out in the prototype stage. The 5S and WISE checklists were assessed. Several action plans were identified based on the assessment results including improvements in material storage and handling, workplace design, machine safety, physical environment, electrical hazard protection, fire prevention, welfarefacilities, and work organization. To guide the implementation, all the proposed actions were divided into short, medium, and long term. The proposed actions were evaluated by the owner and managers. Finally, several short-term actions were implemented.